NEONATAL SCREENING: EDUCATIONAL BOOK ON MATERNAL GUIDANCE (Fiep Bulletin - online, 2013)
The newborn screening or “teste do pezinho” of how popularly known, is a strategy used for the early diagnosis of errors of metabolism before the symptoms become apparent. This study aimed to evaluate the implementation of an educational book on the newborn screening as an instrument of health education for mothers. A data collection was done with 40 mothers in the University Hospital Ana Bezerra (UHAB) Santa Cruz / RN in the months of March to June 2008. Of these 40 mothers 20 were targeted on the test only verbally and 20 beyond the verbal guidance received the book and could handle them in his home. The results confirmed that the book improved the understanding of the interviewed regarding newborn screening
Keywords: Newborn Screening; Education health; Nursing